2022
DOI: 10.1155/2022/9170081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Post Materials and Adaptability on Fracture Resistance and Fracture Mode in Human Endodontically Treated Teeth

Abstract: Objective. To investigate the effect of different post materials and adaptability on fracture resistance and fracture mode of endodontically treated teeth. Materials and Methods. Sixty extracted human mandibular premolars were selected and divided into 6 groups (n = 10) according to the restorative method after endodontic treatment: no ferrule presented and restored without fiber post (Group C), 2.0 mm ferrule presented and restored without fiber post (Group CF), restored with D.T. Light-Post (Group PDT), rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Meanwhile, groups with flared root canals that were restored with anatomically-customized posts (groups 4 and 5) recorded values close to that of the control group (group 1) and had significantly lighter PVS material than groups with flared canals restored with standard, noncustomized posts (group 2, group 3) (see ►Table 2). This outcome is consistent with Bhaktikamala et al17 who reported improved internal adaptation and intimate contact with anatomically-customized FRC posts.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…Meanwhile, groups with flared root canals that were restored with anatomically-customized posts (groups 4 and 5) recorded values close to that of the control group (group 1) and had significantly lighter PVS material than groups with flared canals restored with standard, noncustomized posts (group 2, group 3) (see ►Table 2). This outcome is consistent with Bhaktikamala et al17 who reported improved internal adaptation and intimate contact with anatomically-customized FRC posts.…”
supporting
confidence: 91%
“…Likewise, earlier studies have reported that customized post improved intimate contact and adaptation between the customized post and radicular dentin walls, thus, enhancing frictional retention and leading to a homogenous resin cement layer. 17,23 Additionally, Caceres et al 24 conducted purposive microcomputed tomography to evaluate different cementation techniques and found that relined fiber posts presented with improved adaptation with lower void formation than nonrelined fiber posts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 40 teeth with similar buccolingual root dimensions of 8 ± 0.5 mm and length of 14 ± 0.6 mm distance from the buccal cementoenamel junction (CEJ) to apex were selected after performing measurement using a digital caliper (Mitutoyo Corporation, Kanagawa, Japan) and periapical films. The total sample size was determined using PASS (sample size software) and data from prior research with a similar experimental design [ 13 ]. The suggested sample size was at least eight specimens for each group.…”
Section: Methodsmentioning
confidence: 99%